Reasons to (better) regulate party funding. Beyond political corruption - Sánchez Muñoz, Óscar (EUNOMÍA. Revista en Cultura de la Legalidad, 2022)
Party financing is a key element of the political system. Beyond the response to corruption, the regulation of financing should be aimed at favouring a more open and democratic party model within an egalitarian democracy. The main objectives that such regulation should pursue are to guarantee the sufficiency and stability of party resources, respect for the principle of equal opportunities in electoral competitions, the strengthening of the connection between parties and citizens and also, as another objective, but not the only one, the fight against corruption. This article analyses some of the dysfunctions of the Spanish model of party financing and proposes a profound reform of it.